Elephantopus scaber L. Ethanolic Leaves Extract Modulates IL-2 Production and T-Lymphocyte Activation in Pulmonary Fibrosis Mice Model - Izzah, Fathiyah Nurul; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Rifa'i, Muhaimin; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2024)
Pulmonary fibrosis is a chronic disease characterized by progressive connective tissue deposition that replaces healthy lung tissue. This study aimed to investigate the effect of Elephantopus scaber L. Ethanol Extract (ESEE) treatment on the relative number of IL-2 cytokine and lymphocyte activation in bleomycin (BLM)-induced pulmonary fibrosis mice model. Fifty-six male BALB/c mice were divided into seven treatment groups: N (normal); V or vehicle (corn oil); PF or Pulmonary Fibrosis (BLM 2 mg.kg-1); Dex (Dexamethasone 3 mg.kg-1 + BLM); D1-D3 (ESEE at doses of 0.0504, 0.1008, and 0.2016 mg.kg-1 BW + BLM). ESEE, dexamethasone, and corn oil were administered orally, followed by intraperitoneal bleomycin injection daily for 14 days. Mice were dissected on days 7 and 14, and spleens were isolated to analyze cell populations expressing CD4+IL-2+, CD8+IL-2+, CD4+CD62L+, and CD8+CD62L+. The results showed that bleomycin injection could increase the relative number of IL-2 and decrease the relative number of naive T cells compared to normal mice. ESEE treatment significantly reduced the relative number of IL-2, thus decreasing naive T cell activation after one week of bleomycin injection compared to the mice model. In contrast, the increased IL-2 production led to the increasing naive T cell activation after two weeks of bleomycin injection. Therefore, ESEE treatment has the potential to maintain homeostasis through modulation of IL-2 production and T-lymphocyte activation in the pulmonary fibrosis mice model. Keywords: Elephantopus scaber, IL-2, lymphocytes, mice, pulmonary fibrosis.